Effects of helping relationships on health-promoting lifestyles among patients with chronic kidney disease: A randomized controlled trial. (February 2022) - Chao, Shu-Mei; Yen, Miaofen; Lin, Huey-Shyan; Sung, Junne-Ming; Hung, Shih-Yuan; Natashia, Dhea
Abstract: Background: Healthy behaviors can slow the progression of chronic kidney disease. Professional healthcare providers deliver education, physical exercise programs, motivation consultations, and stage-tailored strategies for improving health behaviors, but their effectiveness reported mixed. The helping relationships of significant others based on the transtheoretical model have been shown to be beneficial in facilitating and practicing health-promoting behaviors. However, few studies have examined the effects of helping relationships on health-promoting behaviors among patients with chronic kidney disease. Objectives: The aim of this study was to examine the effects of the intervention strategies of significant others in their helping relationships with patients to advance stages of exercise and diet behaviors, and to improve health-promoting lifestyles. Design: A randomized controlled study. Settings: Two outpatient nephrology clinics in southern Taiwan. Participants: Sixty participants in each of the two groups. Methods: Patients were randomly assigned to either the intervention group (n = 60) whose significant others received strategies for helping relationships for 12 months, or the control group (n = 60). The Stage of Change of Exercise and Diet Behaviors, and Health Promoting Lifestyle Profile-II Chinese version were assessed at baseline and 3, 6, 9, and 12 months after receiving the helping relationship interventions tailored to stage of change from significant others. Results: Generalized estimating equation analyzes revealed that the intervention group, when compared to the control group, had significantly advanced stages of change in exercise and diet, and improvement in health-promoting lifestyle over time. Adult children and spouses were the most common significant others to help patients practice healthy behaviors, compared to previous studies where professional healthcare providers were the significant others. Conclusions: Individualized plans for healthy behaviors should take into consideration patients' readiness for adopting stage-tailored strategies of helping relationships of significant others to adhere to the health-promoting lifestyle. To promote a healthier lifestyle, significant others, such as spouses and adult children, should be included in treatment programs.